PERSONNEL, LEGAL AND FINANCIAL ASPECTS OF MOTIVATIONAL STRATEGIES OF PERSONNEL MANAGEMENT OF ENTERPRISES IN THE REALITIES OF WARTIME - Hulak, Daniil; Shevchenko, Anna; Kutsenko, Dmytro; Luheria, Serhii (Current Problems of Sustainable Development, 2026)
It is substantiated that an important management task in the personnel management system is currently to reassess and rethink approaches to staff motivation in wartime realities in order to combine in motivational strategies tools and ways to satisfy the interests of different categories of stakeholders in the sphere of labour relations and personnel management of organizations. The purpose of the study was to specify and generalize the personnel, financial and legal aspects of implementing motivational strategies for personnel management of enterprises in wartime realities. To achieve the set goal, the methods of content analysis of professional economic literature, the monographic method, and the generalization method were used. As a result of the study, the influence of war, wartime risks and military actions on staff motivation was outlined, the legal risks and financial consequences for the enterprise from ineffective motivational strategies were specified, proposals were made for adapting classical forms of motivation to wartime realities, and innovative forms of staff motivation were generalized. A list of personnel aspects of motivational strategies for personnel management of enterprises in wartime realities is proposed, which includes: the need to prevent personnel risks by integrating risk management tools into the enterprise’s management system; the formation of clear guidelines for the quantity and quality of personnel necessary for the enterprise to achieve strategic goals, taking into account various scenarios of changes in external environmental trends in wartime realities; the distribution of motivational tools in accordance with the stage of personnel management: planning of personnel indicators, employee onboarding, increasing intellectual capital, developing human resources potential, monitoring personnel work, ensuring personnel reliability, and dismissing employees. The legal aspects of motivational strategies for personnel management of enterprises include: compliance with the working time regime; ensuring proper working conditions in accordance with the legislation; compliance with minimum social guarantees and maintaining the level of wages within regulatory and legal limits; fixing forms of employee motivation in the collective agreement, labour agreements and other documents; ensuring opportunities for employees to rest; guaranteeing occupational safety while at the workplace and on the territory of the enterprise; official employment and transparent remuneration. The financial aspects of motivational strategies of personnel management include: giving preference to non-material forms of motivation, taking into account the resource limitations of enterprises in wartime; developing budgets for financing motivational measures and monitoring their compliance; finding sources of financing for the use of motivational tools; introducing a system of minor but stable periodic revision and increase in the level of remuneration; ranking bonuses and other forms of material motivation depending on the rating of employees’ achievements (monthly and annual).